Case study in using Web 2.0 tools by Greek educators. (1st January 2012) - Vrettaros, John; Tagoulis, Alexandros; Giannopoulou, Niki; Drigas, Athanasios
During the pilot training of Greek educators on the educational exploitation of Web 2.0 tools and their use in classroom, or in distant courses, an empirical study was at the same time realised. This empirical study's main purpose is to investigate if Greek educators with the appropriate training, and due to the changes that the training brings, e.g., increase of self-efficacy, familiarisation, practical implementations, can use Web 2.0 tools in classroom. For this purpose, the Greek educators were introduced and trained in the use of social software tools, such as Facebook, blogs, YouTube and wikis. This paper presents the results of the study.